EVALUATION OF VITAMIN D SERUM LEVELS IN PATIENTS WITH INSOMNIA - Jai Joseph, Maria; V P, Karthik (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The primary objective of the study was to evaluate the link existing between insomnia and low levels of Vitamin D and the secondary objective was to confirm a link between age and insomnia. Methods: The study assessed the Vitamin D serum levels in 50 subjects with insomnia (diagnosed using Pittsburgh Sleep Quality Index [PSQI]) from the outpatient clinic, Department of General Medicine of Sri Ramachandra Medical Center. All subjects fulfilled the eligibility criteria and also signed the informed consent form provided in patient’s native language for their convenience. With all aseptic precautions, 5 ml of blood was collected from the subjects for tyhe measurement of 25-OH Vitamin-D total levels using fully automated chemiluminescent immunoassay. Statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS 1 7.1). Quantitative variables will be expressed as mean Â± standard deviation (SD), and qualitative variables will be expressed as percentage values. Results: All the patients who are insomniacs were deficient of Vitamin D. Of this, 80% were in deficient state (i.e.,>20 ng/ml) and the rest 20% were in the insufficient state (i.e., 20â€“30 ng/ml). Most of the insomniacs were younger adults. As shown in the graph, 27 patients were in between the age group of 20 and 30 years, 13 patients of 50 patients were between 30 and 40 years of age, 4 patients between 40 and 50 years of age, 4 patients between 50 and 60 years of age, and 2 patients were of age between 60 and 70 years. Conclusion: Our results concluded that insomnia has a direct link with Vitamin D deficiency. Male insomniacs who were Vitamin D deficient were 40% more than female insomniacs with Vitamin D deficiency. It was noted that the incidence of increased body mass index and systolic blood pressure was seen among Vitamin D-deficient insomniacs. Insomnia was more prevalent among younger age groups rather than older adults. Global PSQI value evaluated among all Vitamin D-deficient patients was >5, which indicated poor sleep quality.